California community colleges’ journey toward racial equity: understanding the process of addressing systemic racism - Meraz, Angela Marie (Kansas State University, 2022)
The California Community Colleges (CCC) system is the largest, most diverse public college system in the nation. As the system works to improve outcomes for all students, and in response to the racial climate in the United States during 2020, the system’s Chancellor’s Office released a call to action, asking all colleges to address systemic racism by strategizing and taking action to identify and eradicate systemic racial injustice. This study focused on understanding if and how colleges were responding to the call to action. Using an explanatory mixed-methods design, this study was an exploration of ways in which colleges in the CCC system aligned their work with the CCC Chancellor Office’s call to action. Using critical race theory as a theoretical framework, antiracist work occurring at colleges in the CCC was explored through a quantitative survey and qualitative focus group interviews. This study demonstrated which colleges in the CCC system have been addressing systemic racial injustice through policy, practice, or program changes; highlighted factors that led colleges to this focus of change; and revealed processes colleges used to develop, implement, and measure these changes. Through data analysis, four themes were identified: Equity Is Being Addressed Through Antiracist Practices, Antiracism Is a Focus of Planning and Review Practices; Antiracist Work Involves Professional Development for Faculty and Open, Collaborative Dialogue Among Multiple Stakeholder Groups; and Increased Antiracist Dialogue Generates Measurable Action but More Needs To Be Done.
Keywords: Antiracist; Community college; California community college; Institutional racism; Equity; Systemic racism